2008
DOI: 10.1021/jo702417v
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarylphosphonium-Supported Carbodiimide Reagents:  Synthesis, Structure Optimization and Applications

Abstract: New tetraarylphosphonium (TAP)-supported alkyl- and arylcarbodiimides were synthesized and used as coupling reagents for esterification reactions, amidation reactions and dehydration reactions of hydroxyesters. Taking advantage of the solubility properties imparted by the tetraarylphosphonium unit, a simple precipitation and filtration allowed complete separation of the urea by-products. This paper describes the structure optimization study of the various TAP-supported carbodiimide reagents to obtain the desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…161 Charette ''attached'' carbodiimides to tetraarylphosphonium salts as a means of ''tagging'' the reagent. 162 Reaction was carried out in solution phase, before precipitation of the salt with apolar solvents. Several carbodiimides derivatives 192 were synthesised (Fig.…”
Section: Newer Approaches To Amide Bond Formationmentioning
confidence: 99%
“…161 Charette ''attached'' carbodiimides to tetraarylphosphonium salts as a means of ''tagging'' the reagent. 162 Reaction was carried out in solution phase, before precipitation of the salt with apolar solvents. Several carbodiimides derivatives 192 were synthesised (Fig.…”
Section: Newer Approaches To Amide Bond Formationmentioning
confidence: 99%
“…[10,11] Recently, we reported that the tetraarylphosphonium (TAP) unit can be used as a solubility control group to modify and predict the solubility properties of supported reagents and synthetic intermediates. A number of TAP-supported reagents derived from triphenylphosphine, diethyl azodicarboxylate, [12] tributyltin chloride, [13] and dialkylcarbodiimide [14] have been prepared and successfully used in various reactions. Furthermore, the reagents by-products can be removed from the reaction medium by a precipitation/ filtration sequence.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tetraarylphosphonium-tagged carbodiimides 201 have been used recently in a series of reactions including esterifications (Scheme 36), amidations and dehydrations. 79 The reactions were carried out in dichloromethane, in which the tetraarylphosphonium species were highly soluble, and after reaction was complete the addition of diethyl ether caused their complete precipitation. The products 205 were then recovered in high yield and high purity simply by filtration.…”
Section: Solubility-switchingmentioning
confidence: 99%